Anxiety and depressive symptoms among home isolated patients with COVID-19: A cross-sectional study from Province One, Nepal - Pratik Khanal; Kiran Paudel; Suresh Mehata; Astha Thapa; Ramesh Bhatta; Hari Krishna Bhattarai (Public Library of Science (PLoS), 2022)
Home isolated patients infected with COVID-19 might be at increased risk of developing mental health problems. The study aimed to identify the prevalence and factors associated with anxiety and depression among COVID-19 home isolated patients in Province One, Nepal. This was a cross-sectional study conducted between February 17, 2021, to April 9, 2021. A total of 372 home isolated patients from Province One were phone interviewed in the study. Anxiety and depression were measured using a 14-items Hospital Anxiety and Depression Scale (HADS). Multivariable logistic regression analysis was done to determine the risk factors of anxiety and depression. Among home isolated COVID-19 infected participants, 74.2% and 79% had symptoms of anxiety (borderline: 48.7% and abnormal: 25.5%) and depression (borderline: 52.7% and abnormal: 26.3%), respectively. Watching television was significantly associated with lower odds of experiencing symptoms of anxiety and depression. Females had significantly higher odds of having depression symptoms compared to males while ever married, those with COVID-19 related complications, and those taking medicine for the treatment of COVID-19 symptoms had a higher likelihood of exhibiting symptoms of anxiety. A focus on improving the mental health well-being of COVID-19 infected patients in home settings with connection to the health services is warranted with timely psychological interventions.